2020
DOI: 10.1021/acs.jpcc.0c02287
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and Detrapping in Colloidal Perovskite Nanoplatelets: Elucidation and Prevention of Nonradiative Processes through Chemical Treatment

Abstract: Metal-halide perovskite nanocrystals show promise as the future active material in photovoltaics, lighting, and other optoelectronic applications. The appeal of these materials is largely due to the robustness of the optoelectronic properties to structural defects. The photoluminescence quantum yield (PLQY) of most types of perovskite nanocrystals is nevertheless below unity, evidencing the existence of nonradiative charge-carrier decay channels. In this work, we experimentally elucidate the nonradiative pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
(65 reference statements)
3
32
0
Order By: Relevance
“…Figure S5, Supporting Information shows the dynamics on the ns range. As already observed by Vonk et al, [47] the PL decay is multiexponential (τ 1 = 5 ns and τ 2 = 13 ns) due to the NPl subpopulations in the ensemble. Moreover, the bi-exponential function cannot fit the decay curve on long time scales (>100 ns).…”
supporting
confidence: 79%
See 3 more Smart Citations
“…Figure S5, Supporting Information shows the dynamics on the ns range. As already observed by Vonk et al, [47] the PL decay is multiexponential (τ 1 = 5 ns and τ 2 = 13 ns) due to the NPl subpopulations in the ensemble. Moreover, the bi-exponential function cannot fit the decay curve on long time scales (>100 ns).…”
supporting
confidence: 79%
“…This may explain the extended PL lifetimes that have been reported previously in the literature. [ 39,40,47 ] Additionally, we have also demonstrated the importance of capping ligands to prevent the formation of deep trap states. Desorption of the ligand from the surface due to sample aging increases the number of deep trap states and directly influences the PLQY of the NPls.…”
Section: Figurementioning
confidence: 89%
See 2 more Smart Citations
“…1c), indicating that the carrier trapping caused by surface defects in the as-prepared NWs and NPs is negligible. In previous studies, the trapping of carriers in perovskite nanoplates are demonstrated to occur in very fast (ps) time scales, the long radiative lifetimes are attributed to delayed photons from charge detrapping process [25]. In order to verify whether there exists fast trapping process, we performed PL up-conversion (PL-UC) measurement (Fig.…”
mentioning
confidence: 99%